Prevalence of Femoroacetabular Impingement Imaging Findings in Asymptomatic Volunteers: A Systematic Review - Frank, Jonathan M; Harris, Joshua D; Erickson, Brandon J; Slikker, 3rd, William; Bush-Joseph, Charles A; Salata, Michael J; Nho, Shane J (Arthroscopy, 2015)
The aim of this study was to determine the prevalence of radiographic findings suggestive of femoroacetabular impingement (FAI) in asymptomatic individuals. A systematic review was performed using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies reporting radiographic, computed tomographic, or magnetic resonance imaging (MRI) findings that were suggestive of FAI in asymptomatic volunteers were included. Cam, pincer, and combined pathologic conditions were investigated. We identified 26 studies for inclusion, comprising 2,114 asymptomatic hips (57.2% men; 42.8% women). The mean participant age was 25.3 ± 1.5 years. The mean alpha angle in asymptomatic hips was 54.1° ± 5.1°. The prevalence of an asymptomatic cam deformity was 37% (range, 7% to 100% between studies)-54.8% in athletes versus 23.1% in the general population. Of the 17 studies that measured alpha angles, 9 used MRI and 9 used radiography (1 study used both). The mean lateral and anterior center edge angles (CEAs) were 31.2° and 30°, respectively. The prevalence of asymptomatic hips with pincer deformity was 67% (range 61% to 76% between studies). Pincer deformity was poorly defined (4 studies [15%]; focal anterior overcoverage, acetabular retroversion, abnormal CEA or acetabular index, coxa profunda, acetabular protrusio, ischial spine sign, crossover sign, and posterior wall sign). Only 7 studies reported on labral injury, which was found on MRI without intra-articular contrast in 68.1% of hips. FAI morphologic features and labral injuries are common in asymptomatic patients. Clinical decision making should carefully analyze the association of patient history and physical examination with radiographic imaging. Level IV, systematic review if Level II-IV studies.